Studing about the structure and contents of four newspapers(Keyhan,Ettelaat,Etemad and Etemad melli) on related to addiction(1385-1386) - Mahdieh Hamzehee (Drug Control Headquarters, Research and Education Office, 2009)
Objectives: This article considers the structure and content of four newspapers (Keyhan, Ettelaat, Etemad and Etemad melli) on related to addiction during year 1385-1386. The theoretical bases of this article have been based on Agenda Setting theory and Gatekeeping approach. Methods: The method of research has been content analyziz and the variables reviewed in this study are including: the structure and content of addiction-related stories (as dependent variable), stories style , stories subjects, type of narcotic substances in title and lead (as independent variables) that are published and reflacted in these newspapers. Findings: According to the findings,the relation between these press about variables offered was meaningful. A)- Most of newspapers have payed attention to addiction by using news style not reports,articles or interviews."Etemad" has used analyzing styles more than other ones. B)- Most of newspapers's contents are about criminal activities. ."Etemad" has published the most of social and medical contents in related to addiction. C )- Most of drugs which has been mentioned in title and leads has related to illicit narcotic drugs. Results: On the contrary of the drug 'wars' in our country, addiction has remined as a serious threat to the nation's health. Then we should change our ways to eradicate this problem and the media,specially the newspapers, are one key mechanisms to achieve this aim. But the findings of this study shows that the newspapers can't do their responsibilities to addiction problemin * -M.A in Social Communication Sciences ,Allameh Tabatabaee University<mhamzeh7@gmail.com Research On Addiction □280 society by themselves. It is imperative that the newspapers communicate with experts and researchers of medical ,health and Non-Governmental Organizations to amend this dirrections.